ASTRAZENECA VACCINE FATWA AND NETIZEN’S RESPONSES: Indonesian Experience - Faidah, Mutimmatul (Journal of Contemporary Islam and Muslim Societies, 2022)
Abstract: This study is aimed to unravel the da‘wah communication delivered by the Indonesian Ulema Council (MUI) regarding the legal status of Astrazeneca Covid-19 Vaccine (AZD1222) in digital media. This study used qualitative descriptive research design with a virtual ethnographic approach. The AZD1222 Vaccine press conference broadcast online via Youtube channel was the research subject. The research object referred to the effectiveness of MUI da‘wah communication in terms of its communication elements. Data was collected through observations in virtual communities and documentation. The results encompassed five components of digital da'wah in the press conferences, namely da‘i (communicator), mad‘u (communicant), maddah (massage), wasilah (channel) and athar (feedback). The digital media offer people an opportunity to build opinions. Most of them gave negative sentiments because of their misunderstanding of fiqh reasoning. However, mad‘u pragmatism and low fiqh literacy were the main factors for lesser public acceptance of the vaccine. This study recommends further research to examine the vaccine fatwa construction model and fiqh literacy for public. Keywords: da‘wah communication, vaccines, halal, Muslim